2004
DOI: 10.1111/j.1432-2277.2004.tb00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative blood transfusion requirement is the main determinant of early surgical re-intervention after orthotopic liver transplantation

Abstract: Fax: +31-50-3613763 - re-intervention after orthotopic liver transplantationAbstract Liver transplantation is the treatment of choice in selected patients with end-stage liver disease. Postoperative complications often require surgical re-intervention. This study is a retrospective single-centre study to assess the incidence and type of surgical re-intervention during the in-hospital period after liver transplantation and to identify predictors of this re-intervention. From 1994 to 2002, 231 consecutive adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
79
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(91 citation statements)
references
References 24 publications
10
79
2
Order By: Relevance
“…Similar to earlier reports, 10,20 intraoperative transfusion requirement was the most important predictor of reoperative complications after OLT, with other important predictors, including recipient factors (pretransplantation mechanical ventilation, earlier major abdominal operation), donor quality (donor LOS, serum sodium), and operative factors (CIT, WIT). Although it might be impossible to modify each factor individually, recipientedonor matching might allow collective modification of the overall risk of reoperative complications.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Similar to earlier reports, 10,20 intraoperative transfusion requirement was the most important predictor of reoperative complications after OLT, with other important predictors, including recipient factors (pretransplantation mechanical ventilation, earlier major abdominal operation), donor quality (donor LOS, serum sodium), and operative factors (CIT, WIT). Although it might be impossible to modify each factor individually, recipientedonor matching might allow collective modification of the overall risk of reoperative complications.…”
Section: Discussionsupporting
confidence: 85%
“…Data on posteliver transplantation complications specifically requiring reoperation are scarce, with few studies reporting on pre-MELD era cohorts 4,9,10 or limited by sample size. [11][12][13] Although many large series have reported the overall rates of postoperative graft nonfunction; vascular thromboses; and biliary, infectious, and hemorrhagic complications, 5,11,12,[14][15][16][17][18][19] neither the specific management nor the effects of these complications on graft and patient survival are described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Other outcome studies have shown that intraoperative transfusions of plasma products significantly reduce 1-year survival [3][4][5] and increase morbidity in liver transplant recipients. 6 Physicians have used the thromboelastogram (TEG) as a tool for identifying abnormal coagulation. TEG can discriminate between different phases of the coagulation system and is, therefore, useful for identifying clotting abnormalities and guiding the administration of blood products.…”
mentioning
confidence: 99%